Neuropsychiatric toxicity and cycloserine concentrations during treatment for multidrug-resistant tuberculosis - Richard Court; Chad M. Centner; Maxwell Chirehwa; Lubbe Wiesner; Paolo Denti; Nihal de Vries; Joseph Harding; Tawanda Gumbo; Gary Maartens; Helen McIlleron (International Journal of Infectious Diseases, 2021)
Background: Cycloserine, or its structural analogue terizidone, has been associated with neuropsychiatric toxicity (psychosis, depression, and neuropathy). Prospective clinical data on the incidence of and risk factors for neuropsychiatric toxicity in TB patients treated with cycloserine are limited. Methods: A prospective evaluation of neuropsychiatric toxicity was performed using validated screening tools in patients with multidrug-resistant tuberculosis treated with terizidone. Cox proportional hazard modelling was performed to explore the effects of clinical variables and measures of cycloserine pharmacokinetics in plasma. Results: A total 144 participants were recruited: 86 were male and 58 were female; their median age was 35.7 years and 91 (63%) were HIV-infected. Fifty-five (38%) participants developed at least one neuropsychiatric event (30 cases per 100 person-months): 50 (35%) neuropathy, 14 (10%) depression, and 11 (8%) psychosis. Neuropathy was independently associated with cycloserine clearance ((adjusted hazard ratio 0.34 (aHR), P = 0.03)) and high-dose pyridoxine (200 mg vs 150 mg daily, aHR: 2.79, P = 0.01). Conclusions: A high incidence of early neuropsychiatric toxicity was observed in this cohort of patients treated with terizidone. Cycloserine clearance and higher doses of pyridoxine are associated with incident or worsening peripheral neuropathy.